Afterworlds - Westerfeld, Scott (New York : Simon Pulse, 2014)
In alternating chapters, eighteen-year-old Darcy Patel navigates the New York City publishing world and Lizzie, the heroine of Darcy's novel, slips into the "Afterworld" to survive a terrorist attack and becomes a spirit guide, as both face many challenges and both fall in love.
Keywords: Authorship -- Juvenile fiction; Future life -- Juvenile fiction; Dead -- Juvenile fiction; Ghost stories; East Indian Americans -- Juvenile fiction; Lesbians -- Juvenile fiction; Authorship -- Fiction; Future life -- Fiction; Dead -- Fiction; Ghosts -- Fiction; East Indian Americans -- Fiction; Lesbians -- Fiction; New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction